1999
DOI: 10.1177/001440299906500303
|View full text |Cite
|
Sign up to set email alerts
|

Paraeducator Experiences in Inclusive Settings: Helping, Hovering, or Holding Their Own?

Abstract: The perspectives and experiences of20 paraeducators working with inclusion students with disabilities who also present significant behavioral challenges were investigated in this research. The inclusion students were in Grades K through 8 and represented a range of disability categories (e.g., autism spectrum disorder, serious emotional disturbance [SED], learning disability, attention deficit/hyperactivity disorder [AD/HDJ). Findings from this study indicate that paraeducators tend to assume high levels ofres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
118
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(133 citation statements)
references
References 21 publications
15
118
0
Order By: Relevance
“…The existing evidence that paraeducators and parents need to communicate because paraeducators spend more time with the students and thus know them well (French & Chopra, 1999;Marks et al, 1999) was confirmed by this study. However, the findings of this research suggest that an important part of the role of the supervising teacher is to guide and direct the nature of communications.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The existing evidence that paraeducators and parents need to communicate because paraeducators spend more time with the students and thus know them well (French & Chopra, 1999;Marks et al, 1999) was confirmed by this study. However, the findings of this research suggest that an important part of the role of the supervising teacher is to guide and direct the nature of communications.…”
Section: Discussionsupporting
confidence: 78%
“…Third, several authors have stated that the practice of employing paraeducators to facilitate inclusive education of students with disabilities in general education has emerged out of perceived necessity and parental pressure (French & Pickett, 1997;Giangreco et al, 1997;Haas, 1997). Fourth, paraeducators often get to know the students they support better than anyone else at school (Coots, Bishop, & Grentot-Scheyer, 1998;Giangreco et al, 1997;Hanson, Gutierrez, Morgan, Brennan, & Zercher, 1997;Marks et al, 1999). Fifth, paraeducators typically live in the community in which they work and have opportunities to interact with the students and their families in, as well as outside of, school (Chopra et al, this issue; French & Chopra, 1999).…”
Section: Data Collectionmentioning
confidence: 99%
“…A subsequent expansion in professional development opportunities has seen a gradual professionalisation of the TA position with a consequential movement away from a focus upon care and ancillary support for teachers, to one of additional responsibility in relation to classroom pedagogy (Cremin, Thomas & Vincett 2003;Groom 2006). This change, whilst being greeted in positive terms by many within the English education system (Lacey, 2001;Groom & Rose 2005) has also met with some concern because of a perceived lack of enquiry into the effectiveness of TAs or their impact upon efforts to increase inclusion (McVean & Hall, 1997, Marks, Schrader & Levine 1999.…”
Section: Teaching Assistants and Inclusion In Englandmentioning
confidence: 99%
“…Consider that in a study by Marks, Schrader, and Levine ( 1999), paraprofessionals reported their perception that they bore the "primary burden of success" for the students with disabilities with whom they worked and the sense that they were responsible for inclusion of those students. These paraprofessionals reported perceptions that their roles included: (a) not being a "bother" to the classroom teacher, (b) being primarily responsible to provide "on the spot" curricular modifications, and ( c) being expected to be the "expert" for the student.…”
Section: Changing Rolesmentioning
confidence: 99%